(3GdbhGWY ` GdcHjQs - (3SfO Hf Ydjs ((3MGLi (B)(3Ydi GdQGRi(B) s)
(3ChdgG (B:s
(3GYde Cf cd ehdhO jaSO ajg ai SGYI GdehdO RMd KeGfjI CecfI hgj OQLJg hebGHdJg hJQHjYGg hJSOjSGg hJKdjKGg s
(3BNQgG (B:s
(3agh GdehJ dG eMGdI hdG jdJaJ Edi efGSHI GdhbJ dCUd GdYWjI hGdSfI aGYdeg JeJ GdbhGWY GdcHjQ dSfO Hf Ydi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B329 - (3U(B335s
(3HgG fXGe GdJYbjHIs
(3HChd GdeLehYI Jedc SfI (B1249 (3cJHJ gPg GdfSNI fbdkG Yf fSNI LeYgG EHQGgje GdMGSH GdeGdci GdefUhQi GdfGUQi HeOjfI GdbGgQI SfI (B759s
(3Ufa GdeDda gPG GdcJGH YfOeG MVQ YfO GdeCehf Hf gGQhf GdQTjOi GdeJhai SfI (B218(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs